The impact of structured regular physical activity on the development of individual motor skills in school-aged children - Ateljevic, Dalibor; Nanda, Fitri Agung (JUMORA: Jurnal Moderasi Olahraga, 2023)
The research was conducted on a suitable sample of school-aged children (experimental and control group) with the main aim to prove positive impact of the structured regular physical exercises on the development of the individual motor skills. The motor abilities that are specifically covered in this work are speed, strength, coordination and flexibility, which are among the seven basic motor abilities of every healthy individual.In order to get an answer to the question, whether the experimental group differs in terms of the same anthropological characteristics from the control group of respondents at the final measurement compared to the initial measurement, appropriate means, methods and workloads were applied.Applying the method of initial and final measurement, significant differences were found in the motor skills of children from the experimental group of subjects, which basically answered the question of the impact of the application of structured regular physical activity programs on the development of the mentioned motor skills. Keywords: experimental and control group, motor skills, physical activity.